1998
DOI: 10.1111/j.1365-2621.1998.tb15749.x
|View full text |Cite
|
Sign up to set email alerts
|

Metmyoglobin Reducing Capacity of Fresh Normal, PSE, and DFD Pork During Retail Display

Abstract: Fresh pale, soft, exudative (PSE), dark, firm, dry (DFD), and normal pork were stored under light or dark conditions at 4ЊC for 7 days. Sample pH, metmyoglobin reductase activity, oxygen consumption rate, and relative surface metmyoglobin and oxymyoglobin contents were determined. DFD pork had the highest metmyoglobin reductase activity and oxygen consumption rate. Enzyme activity of PSE was lower than that of normal pork, but no difference existed in oxygen consumption rate between PSE and normal samples. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 21 publications
1
30
1
Order By: Relevance
“…Therefore, all the factors responsible for the rate and range of pH decrease after slaughter affect colour changes during storage of meat. During storage, the change in colour is also affected by other factors such as temperature and humidity (Feldhusen & Reinhard 1994), the pressure of oxygen (Livingston & Brown 1982;O'Keeffe & Hood 1982), light (Bertelsen & Skibsted 1987;Zhu & Brewer 1998) and the manner and duration of storage (Rosenvold & Andersen 2003;Lindahl et al 2006). Table 3 presents the effect of the impact of pH u on the change in colour.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, all the factors responsible for the rate and range of pH decrease after slaughter affect colour changes during storage of meat. During storage, the change in colour is also affected by other factors such as temperature and humidity (Feldhusen & Reinhard 1994), the pressure of oxygen (Livingston & Brown 1982;O'Keeffe & Hood 1982), light (Bertelsen & Skibsted 1987;Zhu & Brewer 1998) and the manner and duration of storage (Rosenvold & Andersen 2003;Lindahl et al 2006). Table 3 presents the effect of the impact of pH u on the change in colour.…”
Section: Resultsmentioning
confidence: 99%
“…Rapid pH decline has also been reported to decrease metmyoglobin reductase enzyme activity (Faustman and Cassens 1990). Zhu and Brewer (1998) reported lower metmyoglobin reductase activity and greater metmyoglobin accumulation in PSE pork than in normal and DFD (dark, firm and dry) pork. They speculated that the lower metmyoglobin reductase activity of PSE pork could be due to enzyme denaturation by the rapid pH decline/high temperature condition.…”
Section: Metmyoglobin-reducing Activity and Oxygen Consumptionmentioning
confidence: 99%
“…(5) The precipitation of sarcoplasmic proteins onto myofibrils in pork (Bendall and Wismer-Petersen 1962;Fischer et al 1977Fischer et al , 1979. (6) Denaturation of the myoglobin (globin moiety) (Zhu and Brewer 1998;Sammel et al 2002;Zhu and Brewer 2003).…”
Section: Impacts Of Accelerated Glycolysis At a Higher Than Normal Tementioning
confidence: 99%
“…This accelerated Mb oxidation may be due to accelerated protonation of bound oxygen, which enhances the release of superoxide anions, a known pro-oxidant in meat (Livingston and Brown, 1981). Research on color stability of PSE and DFD pork reported that DFD meat exhibited the highest color stability in comparison to normal and PSE meat, with PSE having the lowest (Zhu and Brewer, 1998). The differences in color stability were attributed to a higher MetMb reducing activity observed for the DFD meat, with the high pH values of the meat maintaining the reducing enzyme activity (Bekhit and Faustman, 2005).…”
Section: Ante-mortem Stressmentioning
confidence: 99%